2014
DOI: 10.1245/s10434-013-3467-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Total Thyroidectomy with Therapeutic Central and Lateral Neck Dissection with a Single Dose of Radioiodine in the Treatment of Regionally Advanced Papillary Thyroid Cancer and Effects on Serum Thyroglobulin

Abstract: Biochemical remission can be experienced in most patients presenting with regionally advanced PTC with total thyroidectomy and compartment based therapeutic neck dissection followed by a single dose of radioiodine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…As supporting data, in a subsequent publication of the same group, the response rate of intermediate-risk cN1b patients to initial therapy was approximately 85% (12). In another series involving N1bM0 patients, the recurrence rate ranged from 15-20% (13)(14)(15)(16)(17)(18), while this rate was approximately 10% in the present series. We attribute this apparent difference to the fact that the present study excluded cN1b patients who additionally exhibited incomplete tumor resection and extensive extrathyroid invasion (pT4) [high risk according to ATA (1)].…”
Section: Last Assessmentsupporting
confidence: 77%
“…As supporting data, in a subsequent publication of the same group, the response rate of intermediate-risk cN1b patients to initial therapy was approximately 85% (12). In another series involving N1bM0 patients, the recurrence rate ranged from 15-20% (13)(14)(15)(16)(17)(18), while this rate was approximately 10% in the present series. We attribute this apparent difference to the fact that the present study excluded cN1b patients who additionally exhibited incomplete tumor resection and extensive extrathyroid invasion (pT4) [high risk according to ATA (1)].…”
Section: Last Assessmentsupporting
confidence: 77%
“…However, our study included a larger number of patients and longer follow-up period than those of previous studies. 18,19 The results of the present study may be of value to guide clinicians in the identification of at-risk patients who would benefit from aggressive treatments and intensive surveillance.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies investigating the outcomes of lateral neck dissection for PTC have reported variable rates of recurrence. 18,19 In one study, the 1-, 3-, and 5-year disease-free survival rates were 94.4, 88.0, and 85.5 %, respectively. 18 Another recent study reported an overall recurrence rate of 18 % (11/61) during a median follow-up of 20 months (range 1-109 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations